2008
DOI: 10.1213/ane.0b013e3181770b42
|View full text |Cite
|
Sign up to set email alerts
|

The Pivotal Role of Vasopressin in Refractory Anaphylactic Shock

Abstract: Standard treatment of anaphylactic shock, including discontinuation of the causative agent, administration of epinephrine, and infusion of IV fluids, did not stabilize cardiocirculatory function, and adding arginine vasopressors resulted in prompt hemodynamic stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 34 publications
1
30
0
1
Order By: Relevance
“…[77][78][79] Other small case series described successful results with administration of alternative ␣-agonists such as norepinephrine, 80 methoxamine, 81,82 and metaraminol. [83][84][85] Alternative vasoactive drugs (vasopressin, norepinephrine, methoxamine, and metaraminol) may be considered in cardiac arrest secondary to anaphylaxis that does not respond to epinephrine (Class IIb, LOE C).…”
Section: Vasopressorsmentioning
confidence: 99%
“…[77][78][79] Other small case series described successful results with administration of alternative ␣-agonists such as norepinephrine, 80 methoxamine, 81,82 and metaraminol. [83][84][85] Alternative vasoactive drugs (vasopressin, norepinephrine, methoxamine, and metaraminol) may be considered in cardiac arrest secondary to anaphylaxis that does not respond to epinephrine (Class IIb, LOE C).…”
Section: Vasopressorsmentioning
confidence: 99%
“…479 A small case series of patients with anaphylactic shock with or without cardiac arrest suggested that patients who did not respond to standard therapy may benefit from vasopressin (LOE 4). 480,481 A few small case series (LOE 4) have described promising initial findings with ␣-agonists such as norepinephrine, 482 methoxamine, 483 terlipressin, 484 and metaraminol. [485][486][487] A few small case reports (LOE 4) of cardiac arrest suggest cardiopulmonary bypass 488,489 or mechanical support of circulation 490 may be helpful in the setting of anaphylaxis.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…[88][89][90] There are multiple case reports describing the use of vasopressin, norepinephrine and methylene blue in patients with anaphylaxis refractory to epinephrine. [91][92][93][94][95][96][97][98][99][100][101] Consensus guidelines recommend the use of an epinephrine infusion if a vasopressor infusion is required for patients with anaphylactic shock.…”
mentioning
confidence: 99%